Model for the knowledge management development in the research area - Salcedo Guzmán, Luisa Elena (2012)
All organizations, whether they belong to the public or private sector, should have the necessary tools to meet the changing environment. The Knowledge Management, which is based on the measurement and evaluation of Intellectual Capital, provides the methodology for this purpose and is a management tool adaptable to any type of organization. However, it is difficult to apply this tool that has been designed for private companies, to the public institutions, especially in national universities. This paper seeks to present the way to apply of a theoretical model management to contribute to the development of scientific production in the Universidad Nacional Mayor de San Marcos, the model is based on Knowledge Management and was adapted to the characteristics of the institution public higher education. This article is the result of literature reviews and is part of the research project “Management model for development of application projects”